Obstructed defaecation syndrome: European consensus guidelines on the surgical management. Issue 10 (17th April 2021) - Picciariello, A; O'Connell, P R; Hahnloser, D; Gallo, G; Munoz-Duyos, A; Schwandner, O; Sileri, P; Milito, G; Riss, S; Boccasanta, P A; Naldini, G; Arroyo, A; et al.
Lay Summary: Clinical decision-making in the treatment of patients with obstructed defaecation remains controversial and no international guidelines have been provided so far. This study reports a consensus among European opinion leaders on the management of obstructed defaecation in different possible clinical scenarios. Abstract : Management of obstructed defaecation is challenging and remains controversial. No international guidelines have been published.